The Quality of Primary Care in Cambodia: An Assessment of Knowledge and Effort of Public Sector Maternal and Child Care Providers - Dan Han; Somil Nagpal; Sebastian Bauhoff (Taylor & Francis Group, 2022)
ABSTRACTImproving the quality of primary care is essential for achieving universal health coverage in low- and middle-income countries. This study examined the level and variation in primary care provider knowledge and effort in Cambodia, using cross-sectional data collected in 2014-2015 from public sector health centers in nine provinces. The data included clinical vignettes and direct observations of processes of antenatal care, postnatal care, and well-child visits and covered between 290-495 health centers and 370-847 individual providers for each service and type of data. The results indicate that provider knowledge and observed effort were generally low and varied across health centers and across individual providers. In addition, providers' effort scores were generally lower than their knowledge scores, indicating the presence of a "know-do gap." Although higher provider knowledge was correlated with higher levels of effort during patient encounters, knowledge only explained a limited fraction of the provider-level variation in effort. Due to low baseline performance and the know-do gap, improving provider adherence to clinical guidelines through training and practice standardization alone may have limited impact. Overall, the findings suggest that raising the low quality of care provided by Cambodia's public sector will require multidimensional interventions that involve training, strategies that increase provider motivation, and improved health center management. The authors reported there is no funding associated with the work presented in this article.